Making touch analog: The prospects and perils of a haptic media studies. (October 2017) - Parisi, David; Archer, Jason Edward
In this article, we argue for the urgency of establishing a coherent tradition of haptic media studies, suggesting that the fields of visual culture studies and sound studies provide analogs, however imperfect, for modeling a new touch-oriented approach to media. This call to make touch like the senses of seeing and hearing echoes previous movements in touch's discursive and institutional history, as investigators in prior generations similarly aspired to transform tactility through the development of new institutionally grounded research programs. Furthermore, we outline one possible genealogy of haptic media that attends specifically to the power relations expressed through the technoscientific harnessing of touch by haptics. We close with a programmatic set of suggestions for operationalizing haptic media studies.